2004
DOI: 10.1128/jcm.42.10.4769-4775.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Increase in Prevalence of Fecal Carriage of Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae during Nonoutbreak Situations in Spain

Abstract: The occurrence of extended-spectrum ␤-lactamase (ESBL)-producing isolates has increased worldwide. Fecal carriage of ESBL-producing isolates has mainly been detected in nosocomial outbreaks, and few studies have evaluated fecal carriage during nonoutbreak situations and among patients in the community. We have studied the prevalence of ESBLs in 1,239 fecal samples from 849 patients (64.1% of whom were ambulatory) in 1991 and have compared the prevalence data with those obtained in 2003 for 400 fecal samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
197
6
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(227 citation statements)
references
References 44 publications
17
197
6
7
Order By: Relevance
“…CTX-M-2 was first characterized and appears to be dominant in Argentina. 20 Studies carried out in Europe have shown that the occurrence of the bla CTX-M-2 group is rare. Recent studies in Southeast Brazil have demonstrated the presence of bla CTX-M-2 gene in K. Pneumoniae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CTX-M-2 was first characterized and appears to be dominant in Argentina. 20 Studies carried out in Europe have shown that the occurrence of the bla CTX-M-2 group is rare. Recent studies in Southeast Brazil have demonstrated the presence of bla CTX-M-2 gene in K. Pneumoniae.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance of ESBL-producing isolates to other classes of antimicrobial agents shown in this report has been confirmed by other studies. 5,20 Among Enterobacteriaceae, these resistance pattern was commonly associated with a few types of integrons.…”
Section: Resultsmentioning
confidence: 99%
“…Os principais gêneros produtores de ESBLs, dentre as enterobactérias, são Escherichia coli, Klebsiella pneumoniae, Proteus sp, Providencia sp e Enterobacter sp 2 . Enterobactérias produtoras de ESBLs estão amplamente disseminadas, já tendo sido reportadas na França, Estados Unidos, Reino Unido, Grécia, Holanda, Hungria, Portugal, Bolívia, Peru, Brasil, entre outros [9][10][11][12][13] .…”
unclassified
“…Der Erreger löst Infektionen in der Regel nur in stark immunsupprimierten Patienten, vor allem Patienten mit soliden und hämatologischen Krebserkrankungen aus [20][21][22][23][24], bei denen die Infektion auch mit einer nennenswerten Letalität verbunden ist [20][21][22][23][24][25] [41].…”
Section: Nicht Behandelte Speziesunclassified